2018
DOI: 10.1016/j.jacr.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fatigue From Overnight Shifts on Radiology Search Patterns and Diagnostic Performance

Abstract: After ONS, radiologists were more fatigued with worse diagnostic performance, a 45% increase in view time per case, a 60% increase in total gaze fixations, and a 34% increase in time to fixate on the fracture. The effects of fatigue were more pronounced in residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 37 publications
4
34
1
1
Order By: Relevance
“…Kundel et al (2007) found a wide range of diagnostic performance across residents, fellows, and attendings when looking at a test set of mammograms. Hanna et al (2018) likewise found that residents could outperform attendings in a fracture detection task under both fatigued and non-fatigued conditions. Lesgold et al (1988) discovered that more advanced residents were occasionally less likely to make a correct interpretation on several complex x-rays compared to more junior residents.…”
Section: Challenges To the Functional Definition Of Expertisementioning
confidence: 75%
See 2 more Smart Citations
“…Kundel et al (2007) found a wide range of diagnostic performance across residents, fellows, and attendings when looking at a test set of mammograms. Hanna et al (2018) likewise found that residents could outperform attendings in a fracture detection task under both fatigued and non-fatigued conditions. Lesgold et al (1988) discovered that more advanced residents were occasionally less likely to make a correct interpretation on several complex x-rays compared to more junior residents.…”
Section: Challenges To the Functional Definition Of Expertisementioning
confidence: 75%
“…Hanna et al (2018) found that after an overnight shift fatigued radiologists demonstrated worse diagnostic performance (with increased false negatives and positives) and increased time to fixate on fractures when examining bone radiographs. Although total viewing time per case was longer for all radiologists when fatigued, the effect was significantly more pronounced with residents compared to faculty members.…”
Section: Eye Movements and Search Patterns In Radiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, exhausting working conditions (long hours, shift work, stressful work environment) result in decreased cognitive performance. Fatigue from overnight hospital shifts resulted in worse diagnostic performance among radiologists, and the mean time to first fixate on a fracture increased by 34% among the fatigued physicians [19]. The link between fatigue and risk of road traffic accidents is well established, including in car drivers [20] and rail freight-regulating employees [21].…”
Section: Fatigue Lack Of Energy and Lower Physical And Cognitive Permentioning
confidence: 99%
“…visuelle Detektionsfähigkeit in der Radiologie nach langen Arbeitstagen bzw. durch Ermüdung nachts nachweisen [11][12][13][14].…”
Section: Wochentagsverteilung Sowie Tages-und Nachtzeitenunclassified